2017
DOI: 10.1016/j.neuroimage.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of participant-level confound regression strategies for the control of motion artifact in studies of functional connectivity

Abstract: Since initial reports regarding the impact of motion artifact on measures of functional connectivity, there has been a proliferation of participant-level confound regression methods to limit its impact. However, many of the most commonly used techniques have not been systematically evaluated using a broad range of outcome measures. Here, we provide a systematic evaluation of 14 participant-level confound regression methods in 393 young adults. Specifically, we compare methods according to four benchmarks, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

43
974
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 909 publications
(1,057 citation statements)
references
References 84 publications
(198 reference statements)
43
974
3
Order By: Relevance
“…This procedure was done separately for men and women ( Sample 1 : 5 males, 5 females; Sample 2 : 4 males, 4 females). No subjects were excluded due to outlier motion parameters (DVARS and FD both displaying zero-centered values) (Salimi-Khorshidi et al 2014; Varikuti et al 2016; Ciric et al 2017). For RSFC analyses, the subject-specific time series for each node of each network were computed as the first eigenvariate of the activity time courses of all gray-matter voxels within 6 mm of the respective peak coordinate.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was done separately for men and women ( Sample 1 : 5 males, 5 females; Sample 2 : 4 males, 4 females). No subjects were excluded due to outlier motion parameters (DVARS and FD both displaying zero-centered values) (Salimi-Khorshidi et al 2014; Varikuti et al 2016; Ciric et al 2017). For RSFC analyses, the subject-specific time series for each node of each network were computed as the first eigenvariate of the activity time courses of all gray-matter voxels within 6 mm of the respective peak coordinate.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Power et al (2014) demonstrated that, in contrast to criticism (Saad et al, 2012), application of GSR actually decreases observed group differences. More recently, GSR has been shown to be especially effective at removing correlations of connectivity with subject motion (Ciric et al, 2017). Given these considerations, we feel GSR is an appropriate processing technique in this study.…”
Section: Methodsmentioning
confidence: 99%
“…“Preprocessing” techniques to ensure that data meet several assumptions prior to analysis. The most standard steps to preprocessing rsfMRI data include slice timing correction [15], motion correction ([16, 17]), realignment [18], coregistration of anatomical and functional images [19], spatial normalization [20], and smoothing [21]. Smoothing increases signal to noise, normalizing error distributions, and accomodates anatomical and functional variation between subjects.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%